Social prescribing for suicide prevention: a rapid review - Dash, Sarah; McNamara, Stella; de Courten, Maximilian; Calder, Rosemary (Frontiers in Public Health, 2024)
This rapid review delves into the realm of social prescribing as a novel approach to suicide prevention by addressing the social determinants of health. Through an exploration of various databases including MEDLINE, PsychInfo, WILEY, and Sage, a total of 3063 articles were initially identified as potentially relevant to the research. Following a meticulous screening process, 13 articles were included in the final review, shedding light on the potential effectiveness and impact of social prescribing interventions on suicide prevention.Key findings indicate the need for additional monitoring and support for individuals at risk of suicide, emphasizing warm referrals and sustained connections after referral to enhance the efficacy of social prescribing models. The review also highlights the importance of social capital and trust among vulnerable populations, underscoring the significance of community-based referrals in suicide prevention initiatives.Overall, this review identifies the potential of social prescribing as a valuable tool in mitigating suicide risk factors and promoting mental health and wellbeing in diverse populations.